Exploring benefits of a collaborative Scottish university-organization alternative credentials approach to re-skilling - Smith, Christopher J. M.; Choromides, Constantinos; Clyde, Alicia; Stewart-Knight, Fiona (Frontiers in Education, 2025)
IntroductionAlternative credentialed forms of learning provide important learning pathways for professionals to up-and re-skill. In Scotland, credit-rating of learning is one option to create these credentialed courses, based on national principles from the Scottish Credit and Qualifications Framework (SCQF) Partnership. However, there is currently almost no evidence on the benefits of such an approach for those involved, so this study focuses on examining the benefits of having a flexible national qualification system (SCQF) that allows ‘credit-rating’ of organizational learning.MethodsAn exploratory research methodology using a single case study design (based on one Scottish university) was used. Nine semi-structured interviews (with both learning providers and university employees) were inductively analyzed using a two-cycle thematic analysis approach to determine themes.ResultsThe SCQF guidance and the business-orientated nature of Scottish universities in credit-rating of learning were highlighted as an important enabler for this alternative form of credentialed learning to being possible. Value to learners focused on having a professionally relevant qualification that had validity, both through possible credit transfer to other programs and providing recognition of competence. Such credit transfer and entry into university programs is a benefit for the university and aligns to Scottish Government priorities of widening access as well as supporting up-and re-skilling. Credit-rating of learning also enhances the credibility of the learning provider’s offering and enhances their own quality assurance processes.DiscussionClear value to a range of stakeholders is created, with the university able to determine its own business model to provide credit-rating of learning, and this flexibility is important to align to institutional strategy, as well as to provide an effective, efficient service. It is recognized that credit-rating of learning co-creates value for the participants, and future research and opportunity lies around exploring this further. Credit-rating of learning has great potential to support national priorities, but this service needs to be better understood by companies and employers for it to reach its potential.